PELATIHAN KADER KESEHATAN DALAM PENINGKATAN SELF CARE MANAGEMENT PASIEN HIPERTENSI - Wedri, Ni Made; Rasdini, IGA Ari (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
Hypertension is a condition where the systolic blood pressure is >140 mmHg and/or diastolic >90 mmHg. Hypertension is the highest risk of stroke and cardiovascular disease. Hypertension cases at the Mengwi I Community Health Center are still high, efforts are being made to control them by promoting healthy living behavior and posyandu for the elderly. The problem is that the presence of elderly people in activities is less than optimal. Self Care Management for Hypertension sufferers is important and necessary to help reduce and maintain stable blood pressure. The service aims to increase health cadres' knowledge about self-care management for hypertension sufferers. Starting from giving a pre-test to cadres through a questionnaire, then providing counseling and self-care management training for hypertension sufferers. Next, the cadres provide direct assistance to hypertension sufferers in each banjar, finally a post test is carried out on the cadres. The result was an increase in cadres' knowledge and abilities regarding self-care management for hypertension sufferers with a good category, namely 100%. It is hoped that health cadres will always implement self-care management for hypertension correctly and sustainably.